Lanthanide-based near-infrared emitting metal–organic frameworks with tunable excitation wavelengths and high quantum yields. Issue 50 (3rd April 2018) - Nguyen, Tu N.; Capano, Gloria; Gładysiak, Andrzej; Ebrahim, Fatmah Mish; Eliseeva, Svetlana V.; Chidambaram, Arunraj; Valizadeh, Bardiya; Petoud, Stéphane; Smit, Berend; Stylianou, Kyriakos C.
Abstract : The introduction of –NH2 group inSION-100 allows the visible light absorption, and bothSION-100 andSION-100-NH2 luminesce NIR light with long lifetimes and high quantum yields. Abstract : We report here two isoreticular ytterbium (Yb) 2D metal–organic frameworks (MOFs) emitting near-infrared (NIR) luminescence with 1.26(2)% quantum yield values, which are among the highest values reported to date for MOFs incorporating NIR-emitting lanthanide cations. The excitation wavelength of the Yb III MOFs can be red-shifted to the visible range by introducing an amino group to the organic chromophore. Density functional theory (DFT) calculations were performed to gain insights into the photophysical properties of this new family of MOFs.